3D carbonaceous nanostructured transition metal nitride, carbonitride and carbide as polysulfide regulators for lithium-sulfur batteries. (November 2022) - Cheong, Jian Liang; Hu, Chen; Liu, Wenwen; Ng, Man-Fai; Sullivan, Michael B.; Ying, Jackie Y.
Abstract: We report a general and straightforward approach to produce high surface area nanomaterials of transition metal nitride, carbonitride and carbide nanoparticles that are highly dispersed on 3D carbonaceous structure. The preparation of these novel nanomaterials involves a simple one-step heat treatment of a metal precursor and urea-derived graphitic carbon nitride mixture under argon, unlike the conventional methods of using ammonia gas to prepare nitride and high-temperature carbothermal reduction of oxide to produce carbide. With this approach, we have synthesized titanium nitride (TiN/C), vanadium carbonitride (V2 CN/C) and niobium carbide-based (NbC/C) nanomaterials using alkoxide precursors. Taking advantage of their high electronic conductivity and surface properties, we have developed the nitrides and carbides as polysulfide (PS) regulators to combat the well-known problems of lithium-sulfur (Li-S) batteries (shuttle phenomena, insulating sulfur, etc. ). In particular, V2 CN/C nanomaterial was found to possess higher redox activity as compared to TiN/C and NbC/C based on density functional theory (DFT) calculations, polysulfide adsorption studies and various electrochemical experiments. V2 CN/C also demonstrated superior performance with an initial specific capacity of 1055 mAh g −1 at 0.2 C and sulfur loading of 4.5 mg cm −2, and a practical areal capacity and capacity retention of ~ 4.2 mAh cm −2 and 89%, respectively, after 300 cycles. Graphical Abstract: ga1